1992
DOI: 10.1002/path.1711680108
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic usefulness of dipeptidyl aminopeptidase IV monoclonal antibody in paraffin‐embedded thyroid follicular tumours

Abstract: Monoclonal antibodies to dipeptidyl aminopeptidase IV (DAP IV, EC 3.4.14.5) were raised and selectively applied to paraffin-embedded sections of thyroid carcinoma. Five monoclonal antibodies were found to stain paraffin sections of thyroid carcinomas. Using one of these antibodies (44-4), we studied retrospectively aberrant expression of DAP IV in thyroid carcinoma to determine whether immunohistochemical staining with DAP IV antibody is useful in pathological diagnosis. In almost all cases of thyroid follicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 20 publications
1
33
1
Order By: Relevance
“…The existence of both negative activity stain- positive by activity staining, the intensity of immunoreactive TPO expression varied from normal to faint levels. Positive staining for DPPIV/CD26 activity can therefore be a histochemical diagnostic marker with which to distinguish FTC from follicular adenoma, as previously mentioned [2]. It can be speculated that histochemically negative staining of the two enzymes is specific to medullary thyroid carcinoma.…”
Section: Dppiv/cd26mentioning
confidence: 70%
See 1 more Smart Citation
“…The existence of both negative activity stain- positive by activity staining, the intensity of immunoreactive TPO expression varied from normal to faint levels. Positive staining for DPPIV/CD26 activity can therefore be a histochemical diagnostic marker with which to distinguish FTC from follicular adenoma, as previously mentioned [2]. It can be speculated that histochemically negative staining of the two enzymes is specific to medullary thyroid carcinoma.…”
Section: Dppiv/cd26mentioning
confidence: 70%
“…RECENT interest in the role of CD26 in various human cancers has been phenomenal, but the role of CD26 in human cancers has been studied previously under different names including dipeptidyl aminopeptidase IV (DAP IV) by Aratake et al [1] and Kotani et al [2,3] and dipeptidyl peptidase IV (DPP IV) by Darmoul et al [4]. In this study, we examined the significance of DAP IV/DPP IV/ CD26 (DPPIV/CD26 hereafter) as a tumor marker for thyroid carcinomas.…”
mentioning
confidence: 99%
“…We have previously reported that follicular adenoma with incomplete capsular invasion had a higher positive incidence than follicular adenoma without incomplete capsular invasion in immunohistochemistry for CD26/DPPIV. 19 It remains unknown whether the increasing expression of these molecules is a consequence or a cause of the acquisition of malignancy. Poorly differentiated follicular subtypes, such as insular carcinoma, express both molecules less intensely when compared with well-differentiated cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some overlapping results, Dipeptidyl aminopeptidase IV (CD26) was reported to be useful for distinction between FTA and FTC, primarily in cytological specimens (Kotani et al, 1992;Maruta et al, 2004). Survivin (Hagh et al, 2006), HBME-1, CD15, thyroid peroxidase, CD10 (a zinc-dependent metalloproteinase, that may share certain functions with some MMPs) and cell proliferation markers have also been reported to be useful ( Cho et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of proapoptotic and/ or activation of antiapoptotic components, including decreased expression of caspase-3 and other caspases has been documented in many cancers shown to correlate with response to treatment and prognosis in some cancers, including those of breast, lung colon, uterine cervix and thyroid. (Kotani et al, 1992;Devarajan et al, 2002;Philchenkov et al, 2004;Fennel et al, 2005;Furuya, 2007;Moradi et al, 2009;) .…”
Section: Discussionmentioning
confidence: 99%